Luminescent Amphiphilic 2, 6‐Bis(1, 2, 3‐triazol‐4‐yl)pyridinePlatinum(II) Complexes: Synthesis, Characterization, Electrochemical, Photophysical, and Langmuir–Blodgett Film‐Formation Studies. Issue 43 (16th September 2013) - Li, Yongguang; Zhao, Le; Tam, Anthony Yiu‐Yan; Wong, Keith Man‐Chung; Wu, Lixin; Yam, Vivian Wing‐Wah
Abstract A new series of platinum(II) complexes with tridentate ligands 2, 6‐bis(1‐alkyl‐1, 2, 3‐triazol‐4‐yl)pyridine and 2, 6‐bis(1‐aryl‐1, 2, 3‐triazol‐4‐yl)pyridine (N7R), [Pt(N7R)Cl]X (1–7) and [Pt(N7R)(CCR′)]X (8–17; R=n‐C4H9, n‐C8H17, n‐C12H25, n‐C14H29, n‐C18H37, C6H5, and CH2‐C6H5; R′=C6H5, C6H4‐CH3‐p, C6H4‐CF3‐p, C6H4‐N(CH3)2‐p, and cholesteryl 2‐propyn‐1‐yl carbonate; X=OTf−, PF6−, and Cl−), has been synthesized and characterized. Their electrochemical and photophysical properties have also been studied. Two amphiphilic platinum(II)2, 6‐bis(1‐dodecyl‐1, 2, 3‐triazol‐4‐yl)pyridine complexes (3‐Cl and 8) were found to form stable and reproducible Langmuir–Blodgett (LB) films at the air/water interface. These LB films were characterized by the study of their surface‐pressure–molecular‐area (π–A) isotherms, XRD, and IR and polarized‐IR spectroscopy.